Evaluation the Use of Distance Learning in Jordanian Universities during the COVID19 Pandemic - Bani Ahmad Bani , Fadi Abdul Raheem Odeh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Various countries have shifted from face-to-face learning to distance learning in response to the challenges imposed by the spread of the COVID19. Worldwide distance learning has become a global phenomenon. The current study aims to evaluate the use of distance learning in Jordanian universities during the covid19 pandemic. The study has developed standards for using distance learning in Jordanian universities and the current status of using distance learning in Jordanian universities. To achieve these aims, the descriptive approach is adopted. A list of the necessary standards for using distance learning is developed, and the current status of using distance learning in Jordanian universities is determined through five domains, and descriptive statistics (means and standard deviations) were calculated as well. The results show the weakness of the technological and human infrastructure necessary for distance learning, and its low ability to create an attractive educational environment, making the use of technology a formal matter that does not achieve the slightest added value to the educational process, along with the weak evaluation of the quality of electronic content. Therefore, the study recommends the necessity of providing modern technological and human infrastructure for higher education institutions to activate them neatly to support the continuity of the educational process.